Accuracy of noninvasive continuous arterial pressure monitoring using ClearSight during one-lung ventilation. Issue 11 (19th March 2021) - Lee, Sang-Wook; Lee, Sangho; Kim, Hyungtae; Kim, Yun-Jong; Kim, Mihyeon; Choi, Jeong-Hyun
Abstract : Abstract: Noninvasive continuous arterial pressure monitoring may be clinically useful in patients who require continuous blood pressure monitoring in situations where arterial catheter placement is limited. Many previous studies on the accuracy of the noninvasive continuous blood pressure monitoring method reported various results. However, there is no research on the effectiveness of noninvasive arterial pressure monitoring during one-lung ventilation. The purpose of this study was to compare arterial blood pressure obtained through invasive method and noninvasive method by using ClearSight during one-lung ventilation. In this retrospective observational study, a total of 26 patients undergoing one-lung ventilation for thoracic surgery at a single institution between March and July 2019 were recruited. All patients in this study were cannulated on their radial artery to measure continuously invasive blood pressures and applied ClearSight on the ipsilateral side of the cannulated arm. We compared and analyzed the agreement and trendability of blood pressure recorded with invasive and noninvasive methods during one-lung ventilation. Blood pressure and pulse rate showed a narrower limit of agreement with a percentage error value of around 30%. In addition, the tracking ability of each measurement could be determined by the concordance rate, all of which were below acceptable limits (92%). In noninvasive arterial blood pressure monitoring using ClearSight, mean blood pressure and pulse rate show acceptable agreement with the invasive method.